WOMEN COUNCILLORS IN LOCAL GOVERNANCE: A STUDY IN SOUTHERN DISTRICT OF WEST BENGAL, INDIA (CAHIERS MAGELLANES-NS, 2024)
The present paper will look into the women as political agents within the local decentralized political system of India. To do so, data is collected, collated and subjective views are interpreted and analysed from two municipal bodies from the southern district of the state West Bengal. The paper would like to observe how the 74th Amendment of Constitution where one third seats got reserved for women, has an impact on women and society at large after 20 years of its implementation. It would also like to observe the gender biases prevailing in the participation of women in the politics of grassroot level in Indian context.In the context of Indian governance, the Constitutional Amendments 73rd and 74th were significant milestones in decentralizing power to local bodies, empowering communities, and promoting grassroots democracy. However, the glaring gender disparity in these bodies called for further reform. The reservation of one-third of local governance seats for women through the 73rd Amendment was a crucial step towards addressing this imbalance and promoting gender equality in decision-making processes. This initiative not only aimed to enhance women’s participation in governance but also sought to bring diverse perspectives and priorities to the forefront of local policymaking. By ensuring women have a meaningful role in decision-making, these amendments not only uphold democratic principles of inclusion and representation, but also contribute to more equitable and effective governance at the grassroots level. West Bengal was one of the first states to adopt the provisions of 74th Amendment of Constitution and in 1995, for the first time during the municipal elections, constituencies were reserved.